Cliques and Capitalism A Modern Networked Theory of the Firm - Lange, Deborah E. De.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2011)
De Lange suggests a new contextually linked building block model to develop theories of the firm in the field of strategy and organizations. Using this approach, she proposes two models: one that is a realistic American version and another that is a futuristic sustainable model. Both are new networked models that integrate current theories; a review of international corporate governance supports the sustainable firm that solves problems of the current one. Through a revised theoretical lens, the book answers a provocative question surrounding modern corporate America: Who wields the power? In this investigative look at the institutional mechanisms behind who is truly running the show, Cliques and Capitalism seeks to not only explain why the current corporate system fails to function well, but also offers solutions for improved corporate governance through a new sustainable model.
Keywords: Management; Organization; Leadership; Business enterprises-Finance.; Economic policy; Behavioral economics; Management; Organization; Business Strategy/Leadership.; Business Finance; Economic Policy; Behavioral/Experimental Economics